THEORETICAL LAW SCIENCE: HISTORY AND MODERNITY - FROLOVA Elizaveta Aleksandrovna (Правовое государство: теория и практика)
The current task of modern jurisprudence is the methodology of theoretical law sciences – sciences, forming legal thinking. The examples of general theory of law, history of political and legal doctrines and philosophy of law show the systematic and genetic nature of the study of law, society and the state. Purpose: historical and theoretical analysis of the nature and function of the sciences of fundamental jurisprudence. Methods: empirical methods of description, comparison, interpretation; theoretical methods of formal and dialectical logic; specific scientific methods: legal-dogmatic and interpretation of legal norms. Results: the study shows that the sciences of fundamental jurisprudence absorb the world experience of all previous centuries in the field of law and state, which creates their theoretical value and relevance in the 21st century. The practical value of theoretical law sciences is due to the fact that the disciplines of this cycle allow for a deeper understanding of the relationship between law and other social regulators, to understand that knowledge of the legal phenomenon should be based on the development of independent assessments and professional attitude to the current law as a dynamically developing system of norms and social r elations.